INTERNATIONAL COURT OF JUSTICE THE LEGAL NATURE OF THE AGREEMENT BETWEEN PARTIES (Law and world, 2017)
In this article, we discussed private international legal relations, including the jurisdiction agreement between parties. Also discussed subjects like international jurisdiction of courts, its notion and difference from the territorial jurisdiction within the country. This article includes sources of international law on competence of courts and the content of material and procedural law with regard to participating parties.